Enzyme/pH dual-responsive polymer prodrug nanoparticles based on 10-hydroxycamptothecin-carboxymethylchitosan for enhanced drug stability and anticancer efficacy. (August 2019) - Pan, Xi; Chen, Jingru; Yang, Mengdan; Wu, Jie; He, Guanghua; Yin, Yihua; He, Meng; Xu, Wenjin; Xu, Peihu; Cai, Weiquan; Zhang, Fanglin
Graphical abstract: (A) Synthesis schematics of Carboxymethylchitosan-10-Hydroxycamptothecin polymer prodrug and (B) processes of its self-assembly and pH/enzyme dual stimuli-response release of drug. Highlights: Amphiphilic 10-hydroxycamptothecin-conjugated carboxymethylchitosan polymer prodrug was synthesized. The nanosystem based on the polymeric prodrug showed pH/enzyme dual response. The system showed very little drug release at pH 7.4 without or with 0.2 μM papain. An accelerated release was observed at pH 5.0 with 2 μM papain (simulating tumor intracellular media). The system showed the potential in the improvement of drug stability and cancer therapy. Abstract: For enhanced stability and anticancer efficacy, the 10-Hydroxycamptothecin (10-HCPT) structure based pH/enzyme responsive polymeric prodrug nanoparticles were constructed by conjugating 10-HCPT to carboxymethylchitosan (CMCS) via pH/enzyme sensitive succinyl linkage followed by ultrasonic dispersion. At pH 7.4 the nanoparticles exhibited a core–shell structure and good in vitro stability with very little drug release. However, upon exposure to pH 5.0, the nanoparticles showed nanogel-like morphology, accompanied by a cumulative drug release rate of up to 71.4% in 60 h in the presence of 2 μM papain, which was nearly two times as much as that in the case of 0.2 μM papain, indicating that enzyme and pH dual-stimulation can significantly elevate tumor cell-selective drug release. In comparison with IC50 of free 10-HCPT, HCPT-g-CMCS nanoparticles exhibited about 4.5 times increase in cytotoxicity on 4T1 cancer cells, while an obviously reduced cell inhibition was observed for healthy liver cell line L-O2. Furthermore, in vitro cell studies confirmed the enhanced intracellular drug release of the system in the 4T1 cancer cells. Hence, the pH/enzyme-sensitive prodrug nanoparticles based on HCPT-g-CMCS may be a promising nano-drug delivery system for cancer therapy.